The Strong Inhibition of Pancreatic Lipase by Selected Indonesian Medicinal Plants as Anti-Obesity Agents - Min Rahminiwati; Dyah Iswantini; Trivadila; Rut Novalia Rahmawati Sianipar; Rani Melati Sukma; Susi Indariani; Anggia Murni (Current Issues in Molecular Biology)
Obesity is characterized by the accumulation of excessive fat, potentially leading to degenerative diseases. Pancreatic lipase, an enzyme responsible for converting 50–70% of dietary fat into monoglycerides, free fatty acids, and various other smaller molecules, plays a crucial role in fat metabolism. Therefore, this study aimed to review selected Indonesian medicinal plants with the potential to inhibit the activity of the pancreatic lipase enzyme. The results showed that kunci pepet (Kaempferiae angustifolia Rosc.), asam gelugur (Garcinia atroviridis), temulawak (Curcuma xanthorrhiza), jombang (Taraxacum officinale F. H. Wigg), pegagan (Centella asiatica), and pala (Myristica fragrans) had strong inhibitory effects, exceeding 50% for both in vitro and in vivo studies. Therefore, further studies are needed to explore the potential of these medicinal plants as anti-obesity treatments.